Optimization of Sports Equipment Procurement in Improving the Quality of Public Services in the Field of Sports in Gelora Tomo City Surabaya - M. Mario Alfian; Ika Devy Pramudiana; Nihayatus Sholichah (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study aims to analyze the optimization of sports equipment procurement in relation to improving the quality of public services in the sports sector in Gelora Tomo, Surabaya City. This study uses the SERVQUAL theoretical approach (Parasuraman, Zeithaml, & Berry, 1988) which includes five main dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The research method used was qualitative-quantitative descriptive with data collection through field observation, documentation, and surveys of 150 respondents who used sports facilities. The results of the study showed that the level of optimization of sports equipment procurement was in the category of quite optimal with an average score of 3.49, while the quality of public services increased to 3.68 (good category). The highest improvement occurred in the tangibles and reliability dimensions, while the empathy dimension still needs to be strengthened through public participation and user-based needs evaluation. Theoretically, these results confirm the relevance of the SERVQUAL model in measuring the quality of public services in the sports sector. Optimizing the procurement of effective, transparent, and needs-oriented equipment has proven to be a key determinant in building inclusive, professional, and sustainable sports public services.